المسؤولية المترتبة عن الأخطاء الناجمة من عملية إعداد السجل العيني - خنفور صابر (Universté ELOUEd-جامعة الوادي, 2020)
على الرغم من ان السجل العيني العقاري لا يصدر الا بعد اصدار سلسلة اجراءات ميدانية تضبطها ترسانة من القوانين والتنظيمات المتمثلة في عملية المسح التي تتم تحت اشراف لجنة خاصة يرأسها قاضي وتتكفل بهذه العملية وكالة وطنية أنشأت خصيصا لتمويل ومتابعة المسح الا ان ذلك لم يخفف من وطأة المشاكل في العقار اكثر من المساهمة في حلها و كثرة النزاعات امام القضاة لكل متضرر من القرارات التي يصدرها كل من المحقق العقاري و المحافظ العقاري من اجل الطعن .Although the real estate registry is not issued except after filed procedures that are set by an arsenal of laws and regulations represented in the survey process that is under the supervision of a special committee headed by a judge and this process is sponsored by a national agency that is specially created to finance and follow up the survey, but this did not alleviate the burden of problems is the property more than contributing to solving them and the many disputes before the judges for each affected by the decisions issued by both the real estate governor in order to appeal them
مذكرة ماستر
Keywords: السجل العيني العقاري -عملية المسح; survey process that is under -the real estate registry is not issued except